Risk of neuropsychiatric disability among painters in the United States. - Brackbill, R M; Maizlish, N; Fischbach, T (Scandinavian Journal of Work, Environment & Health, 1990)
Scandinavian studies have suggested that working with solvents is associated with chronic neuropsychiatric disease. In the United States the Social Security Administration's records of white male recipients of disability compensation were used in a case-referent study on this topic. The cases were defined as men with any one of several neuropsychiatric diseases, and the referents as men with other disabling conditions. The men were considered exposed if they had worked as a painter prior to disability and unexposed if they had worked as a bricklayer. A job-exposure matrix verified the painters' potential exposure to solvents and the bricklayers' lack of potential exposure. The painters had a significant excess of neuropsychiatric disability [adjusted odds ratio (OR) 1.42, 95% confidence interval (95% CI) 1.04-1.94]. Construction painters had an excess of neuropsychiatric disability [OR 1.47 (95% CI 1.07-2.02)] in contrast to spray painters [OR 0.77 (95% CI 0.38-1.54)]. The limitations of the data are discussed, including potential diagnosis bias and exposure misclassification.